(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of two clinical cases of reconstruction in extremely atrophic jaws, classified as class V by Cawood and Howell and subsequent oral rehabilitation with prostheses on implants. Method: Two extremely atrophic jaws were reconstructed using the inverted sandwich technique (TSI), using graft from the anterior iliac crest as the donor area and subsequent oral rehabilitation with prostheses on implants, with follow-up for 2 and 6 years. Results: Despite the severe atrophy, the cases showed satisfactory evolution, without complications, with good bone volume, which allowed the installation of implants with appropriate dimensions and subsequent manufacture of fixed prostheses, without significant resorption after functional load. Conclusion: TSI was effective in the reported cases, and should be considered in cases of major atrophy, to improve the predictability of rehabilitation and minimize the chances of bone fractures when implants are installed without adequate reinforcement.